Standardization of media for tray nursery technique in rice - Greeshma V Mathew (Department of agronomy, College of horticulture, 2015)
Rice is the principal food crop of Kerala. But the cultivated area of rice in Kerala is drastically decreasing year after year. The major reason for reduction in area is the high cost of cultivation due to increased wage rate prevailing in the state. Mechanization has become imperative to sustain and make rice cultivation economically viable as well as ecologically harmonious. Manual transplanting is labour intensive and mechanical transplanting using tray nursery which is a low cost technology can be adopted in rice cultivation. The success of mechanical transplanting depends on the success of nursery. The soil media used for raising tray nursery limits the easy transportation of the nursery and substitution of the growing media with light weight, cheap and easily available materials will lead to the commercial production of paddy mat nursery for easy transportation and wider acceptance of the technology. The present study entitled “Standardization of media for tray nursery technique in rice” was conducted during 2013-2015 at Agricultural Research Station, Mannuthy with the objectives of standardizing the media for tray nursery technique in rice and to evaluate its efficiency under field condition. The study was carried out in two experiments. The variety used was Jyothi. The design of the Experiment I was CRD with 18 treatments replicated five times. The components viz. four levels of rice husk charcoal, seven levels of soil and two levels of vermi compost or coir pith compost were mixed as per the treatments. Observations on mean germination time, growth characters of seedlings, mat characteristics, physico-chemical properties of media, nutrient contents and uptake by the seedlings were recorded. Economics of nursery was also calculated. The media comprised of 80% RHC + 20% VC, 60% RHC + 20% soil + 20% VC, 80% RHC + 10% soil + 10% VC and 80% RHC + 20% CC were found to be superior with respect to biometric characters. The mats with light weight were produced by the media of 80% RHC + 20% CC and 80% RHC + 20% VC. The stronger mats were noticed in the media of 80% RHC + 20% CC and 40% RHC + 40% soil + 20% VC. Based on the growth characteristics, mat characters and nutrient uptake by the seedlings, ten high ranking media were selected among 18 media from Experiment I for evaluating under field condition. The Experiment II was designed to evaluate the ten best performing media selected from Experiment I under field condition. The design was RBD with three replications. Observations on performance of transplanter, growth characters, yield attributes and yield were recorded. The nutrient contents of the crop were determined and uptake by the crop and economics of cultivation were computed. The performance of the transplanter with respect to the number of hills per metre run and the plant population per m2 at planting were comparable in all the media except the media 60% RHC + 20% soil + 20% VC. The optimum number of seedlings per hill and less number of missing hills per m2 were noticed in the media of 80% RHC + 20% VC, 60% RHC + 30% soil + 10% VC, 80% RHC + 20% CC and 20% RHC + 60% soil + 20% VC. The variation in biometric characters, yield attributes, yield, harvest index, nutrient contents of crop and uptake of nutrients by the crop did not produce significant variation under field condition. From the study, it was revealed that the media comprised of 80% RHC + 20% VC, 60% RHC + 30% soil + 10% VC and 80% RHC + 20% CC were found to be better for cheap, good qualty and light tray nursery production in terms of seedling and mat characteristics and performance of transplanter. These media were also noticed to be performing well and produced higher grain yield under field condition also.